Stomach Content Analysis of Channa lucius from the Kampar Lama Oxbow Lake, Mentulik Village, Kampar Regency Riau - Ririn Sofiani; Ridwan Manda Putra; Windarti Windarti (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT Channa lucius is one of freshwater fishes that inhabit the Kampar Lama Oxbow Lake. This research aims to determine the type of food present in the fish’s stomach. To understand the type of food consumed by C. lucius, a research has been conducted at July to August 2019. There were 107 fishes captured, but only 38 fish have full stomach. The analysis was conducted using a gravimetric method. Stomach content was analysis as a basis to calculate the Preponderance Index (PI).  Result shown that the main food of C. lucius is fish (PI 98%) and the complementary food is insects (PI 1%). The water quality parameter of the Kampar Lama Oxbow Lake are as follows : temperature 28-29°C, transparency 47.5-48 cm, pH 5, DO 4.06-4.47 mg/L, and CO2 9.98-11.98 mg/L.Keyword : Channidae, gut content, gravimetric method, index of preponderance